CHARACTERIZATION AND DETECTION OF BEEF FAT ADULTERATION IN DAIRY MILK FAT USING RHEOLOGICAL BEHAVIOR - KALAIMANI, PRIYA SUBRAMANIAN; KALAKANDAN, SURESH KUMAR; THAMBURAJ, SUMAN; PALANIVEL, RAJENDRAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Adulteration investigation using rheological characteristics of DMF (Dairy milk fat) with melted beef fat at various temperatures been evaluated. The change in properties of steady shear and dynamic shear were measured range of 0.01 to 100% by varying strain of 0.1-100 radian per seconds respectively. Generally, DMF resembles the non-Newtonian fluid with flow behavior index (n) for shear thinning fluid of 0.224 to 0.911. The rate of shear ranged 0 to 100/s, dynamic viscosity values decreased DMF, 10%, 20%,30% and 100% adulterated beef fat from 39 to 0.309, 0.591 to 0.103, 0.331 to 0.251, and 0.115 to 0.0858 and -22.1 to -0.65 Pa.s at 36°C, respectively. Herschel–Buckley model optimized to detect the concentration of adulteration with the shear and stress values at R2 ≤ 0.995. The whole value of dynamic viscosity (η*) is more than value of steady viscosity (η) at the pure DMF and concentration of 10% adulteration.